Daidzein alleviates skin fibrosis by suppressing TGF-β1 signaling pathway via targeting PKM2 - Xiaowei Guo; Wenqi Li; Wei Ma; Yuming Liu; Zhigang Liu; Ran Jiao; Zhongyi Yang; Tiantian Zhang; Hongliang Wu; Xiaoyu Ai; Xiaoting Gu; Wendi Wang; et al. (Scientific Reports)
Abstract Skin fibrosis including keloids, which are characterized including excessive deposition, abnormal proliferation, aggressiveness, and migration of the extracellular matrix of dermal fibroblasts. TGF-β signaling is a classical pro-fibrotic pathway, and it plays a crucial part in the occurrence and progression of skin fibrosis. Daidzein (Dai), an isoflavone compound, has been proved to possess anti-fibrosis effect by TGF-β signaling in various inflammatory and fibrotic diseases. However, little is known about Dai on skin fibrosis. Therefore, we further explored the potential effects and mechanisms of daidzein on skin fibrosis. As expected, Dai suppressed proliferation, migration and activation mouse primary dermal fibroblasts and keloid fibroblasts. Meanwhile, Dai also ameliorated bleomycin-induced skin fibrosis and reduced fibrotic markers of keloid tissues. In addition, Dai could target PKM2 to inhibit TGF-β1/Smad signaling in skin fibrosis. Overall, our research demonstrated that Dai might become a potential therapeutic candidate drug for skin fibrosis.